2007
DOI: 10.1007/s00436-007-0734-1
|View full text |Cite
|
Sign up to set email alerts
|

Bather density and levels of Cryptosporidium, Giardia, and pathogenic microsporidian spores in recreational bathing water

Abstract: The study demonstrated that the resuspension of bottom sediments caused by bathers and their direct microbial input resulted in elevated levels of Cryptosporidium parvum oocysts, Giardia lamblia cysts, and microsporidian spores, particularly Enterocytozoon bieneusi, in recreational beach water on days deemed acceptable for bathing by fecal bacterial standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…It is accepted that infection occurs via the fecal-oral route for intestinal microsporidia such as E. bieneusi and E. intestinalis, as spores of these species are shed in the feces, but they can also often be shed in the urine from disseminated infections of the kidney. This is supported by the finding of E. bieneusi and E. intestinalis spores in recreational bathing water alongside oocysts of other enteric pathogens (94,95,114).…”
Section: Microsporidiamentioning
confidence: 68%
“…It is accepted that infection occurs via the fecal-oral route for intestinal microsporidia such as E. bieneusi and E. intestinalis, as spores of these species are shed in the feces, but they can also often be shed in the urine from disseminated infections of the kidney. This is supported by the finding of E. bieneusi and E. intestinalis spores in recreational bathing water alongside oocysts of other enteric pathogens (94,95,114).…”
Section: Microsporidiamentioning
confidence: 68%
“…E. bieneusi was also identified in seawater, lakes and rivers and is common in waste water (Sparfel et al, 1997). Graczyk et al (2007c) detected this pathogen in samples from recreational bathing area. In another study of surface and coastal waters in Ireland were surveyed E. bieneusi, along with Encephalitozoon intestinalis and…”
Section: Enterocytozoon Bieneusimentioning
confidence: 98%
“…Thurston- Enriquez et al (2002) discovered humanpathogenic E. intestinalis in irrigation water. Graczyk et al (2007c) found spores of this pathogen in water from recreational bathing area in USA. It was also detected along with E. hellem in molluscan shellfish from Ireland (Lucy et al, 2008).…”
Section: Encephalitozoon Sppmentioning
confidence: 99%
“…Very large numbers of cryptosporidial oocysts can occur in the faeces of infected animals (up to 10 9 /g) and inputs into marine environments can occur via freshwater (Fayer et al, 2004) from human sewage and bathers (both C. parvum and C. hominis; (Graczyk et al, 2007), from livestock, domestic and wild animals including rodents (C. parvum). Cryptosporidium has been detected in marine mammals (Hughes-Hanks et al, 2005;Rengifo-Herrera et al, 2010) although their infectiousness to humans is poorly understood, however C.hominis has been detected in a dougon in Australia (Morgan et al, 2000).…”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%
“…parvum oocysts can be concentrated by filter-feeding shellfish and survive for at least 30 days (Giangaspero et al, 2005;Graczyk et al, 2006;Graczyk et al, 2007;Guiguet Leal et al, 2008). Oocysts have been shown to survive for at least 12 months in seawater (Tamburrini and Pozio, 1999), but will be affected by temperature, salinity and amount of UV light (Nasser et al, 2007).…”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%